The Influence of Brand Image on the Decision to Use Services through Trust as a Mediation Variable at PT Nabila Berkah Konsultan (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of brand image on service usage decisions with trust as a mediating variable at PT Nabila Berkah Konsultan, a professional services company engaged in planning, licensing, and business legality. Although the company has adequate experience and technical competence, initial observations indicate that brand image and consumer trust levels have not been optimally formed, resulting in inconsistencies in consumer decisions in using the company's services. Therefore, this study aims to examine the direct influence of brand image on trust and service usage decisions, as well as the indirect influence of brand image on service usage decisions through trust. This study uses a quantitative approach with a causal associative research design. Data were collected through the distribution of structured questionnaires to 133 respondents who are consumers of PT Nabila Berkah Konsultan in the past two years. Structural Equation Modeling–Partial Least Squares (SEM-PLS) is the data analysis method used. The findings indicate that trust has a major impact on choices about service consumption, and brand image has a favourable and considerable impact on trust. Furthermore, it has been shown that judgments about the use of services are directly influenced by brand image, but trust serves as a partial mediating factor in this connection. These findings indicate that a strong brand image can build consumer trust, ultimately strengthening their decision to use a service. Therefore, enhancing brand image through consistent service quality, professionalism, and trust-building strategies are crucial factors in encouraging continued service use.